TWO-STAGE INSTALLATION FOR DEEP AIR PURIFICATION FROM FINE-DISPERSED SOLID PARTICLES - Khurmamatov, Abdugafor; Alimardonov, Khusniddin; Akhmedova, Kumush (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
This work presents the results of an experimental study on a two-stage installation designed for deep purification of dust-laden air containing fibrous and fine-dispersed mineral particles. The experimental system consists of a cyclone equipped with a string-type coagulator and a scrubber with a moving (floating) packing. The effects of dust–air flow velocity, structural parameters, and operating conditions on air purification efficiency and hydraulic resistance were investigated. The results showed that as the inlet flow velocity increases from 12 to 17 m/s, the purification efficiency rises up to 99.9%, while further increasing the velocity to 20 m/s causes a decrease in efficiency due to the breakdown of coagulated dust aggregates. The optimal air velocity for the two-stage system was found to be 17 m/s, corresponding to a total hydraulic resistance of 820 Pa. Fractional efficiency analysis revealed that particles larger than 60 µm were removed with almost complete efficiency (99.98%), whereas for particles smaller than 5 µm, efficiency reached 86.6%. These findings confirm that the developed two-stage system ensures high purification efficiency while maintaining acceptable energy consumption and compliance with sanitary standards.